Satisfaction with the Basic Music Course: An Exploratory Study on the Perceptions of Students in the Articulated and Supplementary Regimes - Sousa, Rúben (2022)
The objectives of this investigation were to know and analyze the levels of satisfaction of students with the Music Basic Course at the Conservatory – Madeira’s Professional School of the Arts, in both the articulated and supplementary regimes. Based on a quantitative methodology, a set of sociodemographic variables, musical aptitudes and tastes were analyzed, and positive correlations were found with the satisfaction rates obtained in the disciplines of Instrument